Fatores críticos de sucesso para a implementação de um centro de pesquisa universitária em project studies - Santos, Márcio José dos (2024)
Universities and companies have increasingly been encouraged to collaborate in research activities and knowledge production. University Research Centers bridges academia and the market, generating prestige and revenue for institutions. The field of Project Studies, which is dedicated to the analysis of projects and understanding of project-oriented organizations, has grown significantly in recent decades. This study examines how critical success factors influence the implementation of a University Research Center in Project Studies, focusing on the Graduate Program in Project Management at the Universidade Nove de Julho. In doing so, it aims to enable a strategy for establishing a University Research Center in Project Studies. The methodology employed combined a systematic literature review and a multiple case study. The systematic literature review was based on articles from the Web of Science and Scopus databases. The multiple case study, conducted in four Brazilian universities with established University Research Centers, utilized interviews with experts, document analysis, and archival records to identify the critical success factors present in the implementation of their respective University Research Centers, thereby deepening the analysis. The findings revealed that financial support, the establishment of external partnerships, and the definition of a clear mission, vision, and objectives are essential for implementing a University Research Center. Other relevant factors include leadership, institutional alignment, external visibility, adequate infrastructure, and knowledge management. The research also identified the importance of emerging factors in the Brazilian context, such as merit recognition, contextual understanding, equity and diversity, and planning. The study concludes that the implementation of a University Research Center in Project Studies is a process that requires careful analysis of critical success factors and the specific contingencies of each institution. It contributes to the consolidation of Project Studies as a research field and provides insights and guidance for the establishment of University Research Centers, considering the Brazilian context.